# Form the differential equation of the family of curves represented by the equation (a being the parameter):i. (2x + a)2 + y2 = a2ii. (2x – a)2 – y2 = a2iii. (x – a)2 + 2y2 = a2

(i)

(2 x + a)2 + y2 = a2

On differentiating, with respect to x we have,

Putting this value of a in the given equation we get,

ii. (2 x – a)2 – y2 = a2

4x2 + a2 – 4ax – y2 = a2

4x2 – 4ax – y2 = 0

4ax = 4x2 – y2

On differentiating with respect to x we get,

iii. (x – a)2 + 2 y2 = a2

On differentiating, with respect to x we have,

Putting this value of a in the given equation we get,

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Interactive Quiz on DIfferential CalculusFREE Class
Functional Equations - JEE with ease48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses